Supply Chain Agility Evaluation Using Fishbone Method - Rahman, Dewi Sofiah (Fakultas Pendidikan Ekonomi dan Bisnis, 2021)
The publishing industry is considered as an industry that has a low entry barrier. Supply chain agility refers to the level of speed that the supply chain uses to respond to customer needs. Supply chain agility represents the ability of an organization's internal supply chain functions to provide strategic advantages and innovations to respond to market uncertainty. Supply chain agility is also considered as a key element of an organization's competitive strategyÂ which requires an evaluation method. Fishbone Diagrams or Cause and Effect Diagrams are one of the tools of QC 7 tools that are used to identify and show the relationship between cause and effect in order to find the root causes of a problem. This study used